Gender earnings gaps in the world - Hugo \~Nopo; Nancy Daza; Johanna Ramos (Institute for the Study of Labor (IZA), 2011)
This paper documents gender disparities in labor earnings for sixty-four countries around the world. Disparities are partially attributed to gender differences in observable socio-demographic and job characteristics. These characteristics are used to match males and females such that gender earnings disparities are computed only among individuals with the same characteristics, as in \~Nopo (2008). After comparing males and females with the same characteristics we found that the earnings gap falls within a range between 8% and 48% of average females' earnings, being more pronounced in South Asia and Sub-Saharan Africa. The unexplained earnings gaps are more pronounced among part-time workers and those with low education.
urn:nbn:de:101:1-201106013789
Keywords: C14; D31; J16; O57; 330; gender; wage gaps; matching